2010
DOI: 10.1103/physrevb.82.134413
|View full text |Cite
|
Sign up to set email alerts
|

Effects of interparticle interactions in magneticFe/Si3N4granular systems

Abstract: An experimental evidence of the progressive modification in the magnetic behavior of granular Fe/ Si 3 N 4 samples due to interaction effects between particles is reported. Microstructural features and local structure were determined by x-ray absorption spectroscopy and transmission electron microscopy to select granular samples with predetermined cluster size. Fe/ Si 3 N 4 systems have been characterized by ac-and dcmagnetization measurements to study the gradual evolution of magnetic properties of granular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 51 publications
2
20
0
Order By: Relevance
“…These properties in thermomagnetic ZFC/FC curves are associated with a ferromagnetic behavior. [15][16][17][18][19]28 A similarly shaped ZFC curve, as a result of strong ferromagnetic correlations between particles, has also been observed by Sousa et al 28 in granular CoFe=Al 2 O 3 multilayers and by JimenezVillacorta et al 19 in Fe/Si 3 N 4 multilayers. Hansen et al…”
Section: B Magnetic Properties Of Pristine Fe Nanoparticles and Fe@smentioning
confidence: 63%
See 2 more Smart Citations
“…These properties in thermomagnetic ZFC/FC curves are associated with a ferromagnetic behavior. [15][16][17][18][19]28 A similarly shaped ZFC curve, as a result of strong ferromagnetic correlations between particles, has also been observed by Sousa et al 28 in granular CoFe=Al 2 O 3 multilayers and by JimenezVillacorta et al 19 in Fe/Si 3 N 4 multilayers. Hansen et al…”
Section: B Magnetic Properties Of Pristine Fe Nanoparticles and Fe@smentioning
confidence: 63%
“…At lower concentrations of Fe nanoparticles, a collective freezing of the magnetic moments was observed; whereas at higher concentrations, direct exchange interactions were present between Fe nanoparticles. Jim enez-Villacorta et al 19 reported evidence of modification of the magnetic behavior of NPs evoked by the interaction effects between Fe clusters in granular Fe/Si 3 N 4 particles. The sample with very small Fe cluster dimensions showed superparamagnetic features due to weak dipolar interactions; while in the sample with larger Fe clusters, stronger interactions led to superferromagnetism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 On the other hand, some interpretations have considered that the blocking and reorientation processes exhibited in magnetothermal curves are associated with the superspin reorientation, 20,21,22 and that even the de Almeida-Thouless evolution of the energy barriers can be considered to be an effect of interparticle and/or core-shell interactions. 23,24 In this paper, we present a detailed study, using the microscopic information gained from x-ray magnetic circular dichroism (XMCD), on the magnetic reorientation processes in a transition-metal core-oxide shell system that exhibits spin-glass-like features at low temperatures. It has been reported that sputtering deposition of iron on cooled substrates at temperatures far below room temperature induces a granular structure and thus a granular magnetic behavior in these materials.…”
mentioning
confidence: 99%
“…An ultimate state in the magnetic transitions is the formation of superferromagnetic entities at high concentration of nanoparticles. The formation of superferromagnetic chain like entities has been observed both in ordered as well as disordered arrangement of magnetic particles in a matrix through a systematic increase of concentration/density [11][12][13][14][15][16][17][18][19] . In all the studies reported so far the major emphasis has been to control the absolute size and size distribution of the nanoparticles such that they remain in a single state of magnetic order and probe the static and dynamic behavior of this state.…”
Section: Introductionmentioning
confidence: 99%